Correlation between clinical findings and magnetic resonance imaging findings in meniscal and anterior cruciate ligament injuries - Balemane, Sharath; Ananthraj, Samuel; Ahmad, Humam; Usman, Jassim; Jebbar, Jithin (International Journal of Research in Orthopaedics, 2022)
Background: This study aims to compare the correlation between clinical findings and magnetic resonance imaging with arthroscopic findings in meniscal and anterior cruciate ligament (ACL) injuries. Methods: This was a prospective study of 60 patients with ACL and meniscal injuries of the knee who were admitted between October 2020 and October 2021, who underwent clinical examination, MRI, and arthroscopy of the knee. Results: In our study of 60 cases, there were 44 male and 16 female patients ranging from 18 to 45 years, with the majority of patients between the ages of 25 and 35. The clinical examination had a sensitivity of 88%, specificity of 100%, and accuracy of 90% for ACL, the sensitivity of 80%, specificity of 100%, and accuracy of 90% for medial meniscus, and sensitivity of 50%, specificity of 100%, and accuracy of 83.33% for lateral meniscus. Magnetic resonance imaging (MRI) had a sensitivity of 100%, specificity of 100%, and accuracy of 100% for ACL, the sensitivity of 100%, specificity of 66.67%, and accuracy of 83.33% for medial meniscus, and sensitivity of 100%, specificity of 85%, and accuracy of 90% for lateral meniscus. Conclusions: In conclusion, the current investigation emphasizes the importance of clinical diagnosis, as the positive predictive value (PPV) for all lesions is high. An MRI provides an additional diagnostic tool for ligament and meniscal injuries of the knee. The diagnostic accuracy of all lesions was in the 90th percentile. Because the negative predictive value (NPV) for all lesions is substantial, MRI is utilized to confirm the diagnosis and rule out pathology.